Confronting the "fraud bottleneck": private sanctions for fraud and their implications for justice. Issue 3 (21st September 2015) - Button, Mark; Wakefield, Alison; Brooks, Graham; Lewis, Chris; Shepherd, David
Abstract : Purpose: – The purpose of this paper is to illustrate the ways in which contemporary organisations are imposing their own private sanctions on fraudsters. Design/methodology/approach: – The research draws on primary data from interviews with counter fraud practitioners in the UK, secondary sources and case examples. Findings: – Such developments have been stimulated, at least in part, by the broader limitations of the criminal justice system and in particular a "fraud bottleneck". Alongside criminal sanctions, many examples are provided of organisations employing private prosecutions innovative forms of civil sanction and "pseudo state" sanctions, most commonly civil penalties comparable to fines. Research limitations/implications: – Such changes could mark the beginning of the "rebirth of private prosecution" and the further expansion of private punishment. Growing private involvement in state sanctions and the development of private sanctions represents a risk to traditional guarantees of justice. There are differences in which comparable frauds are dealt with by corporate bodies and thus considerable inconsistency in sanctions imposed. In contrast with criminal justice measures, there is no rehabilitative element to private sanctions. More research is needed to assess the extent of such measures, and establish what is happening, the wider social implications, and whether greater state regulation is needed. Practical implications: – Private sanctions for fraud are likely to continue to grow, as organisations pursue their own measures rather than relying on increasingly over-stretched criminal justice systems. Their emergence, extent and implications are not fully understood by researchers and therefore need much more research, consideration and debate. These private measures need to be more actively recognised by criminal justice policy-makers and analysts alongside the already substantial formal involvement of the private sector in punishment through prisons, electronic tagging and probation, for example. Such measures lack the checks and balances, and greater degree of consistency as laid out in sentencing guidelines, of the criminal justice system. In light of this, consideration needs to be given to greater state regulation of private sanctions for fraud. More also needs to be done to help fraudsters suffering problems such as debt or addiction to rebuild their lives. There is a strong case for measures beyond the criminal justice system to support such fraudsters to be created and publicly promoted. Originality/value: – The findings are of relevance to criminal justice policy-makers, academics and counter fraud practitioners in the public and private sectors.